The Role of Calling and Perceived Organizational Support in the Work Engagement of Private Employees during the COVID-19 Pandemic - Bagus Riyono; Regina Giovanny Sujadiyanto (Faculty of Psychology, Universitas Gadjah Mada, 2023)
The Covid-19 pandemic affected the industrial sector by decreasing productivity, including in private companies. Some private companies have laid off their employees to achieve company efficiency. This situation drives a threat that is arising insecurity, anxiousness, and decreasing engagement among employees. This research aims to understand the role of calling and perceived organizational support (POS) toward work engagement. The research participants are 144 employees from private companies working for at least six months, and they work from home (WFH). This study hypothesizes that POS and calling predict work engagement in a positive direction. Multiple regression analysis was utilized in this study. Results showed increased calling and POS followed by increased work engagement. The implication of this study has two directions; the first is for the organization to improve perceived organizational support, and the other hand, the employee needs to internalize the calling more.